PENGARUH EFEKTIVITAS BEASISWA TERHADAP PRESTASI AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Arief Maulana Azzahri; Sri Kartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine how much the effect of scholarship effectiveness to the academic achievement of students of Economic Education Studies Program FKIP University of Riau. The population in this study are students of Economics Education 2014 until 2016 is 104 participant, and the sample of 83 people. Measurement of data using questionnaires and documentation. The data analysis used is simple linear regression. The results showed the effectiveness of scholarship has a significant effect on the academic achievement of students of Economic Education Studies Program FKIP University of Riau. This can be seen from the regression coefficient, ie the value of constanta (a) of 2.705 and the value of regression coefficient (b) of 0.011. Judging from the calculation of R2 (R Square) obtained value of 0.275. The meaning is that the contribution of scholarship effectiveness influence to the academic achievement of 27.5% and the rest influenced by other factors.Keywords : Effectiveness, Scholarship, Academic Achievement